Mobility Influences During Managerial Career Stages - Veiga, John F. (Academy of Management Journal, 1983)
A multivariate framework was used to determine the impact of 22 individual/career related factors on career mobility. Career mobility was represented by two criterion variables, rate of movement and propensity to move. Several of the 22 factors were found to explain substantial portions of variance in both criterion variables.